Salvianolic Acid B Reduces the Inflammation of Fat Grafts by Inhibiting the NF-Kb Signalling Pathway in Macrophages. (20th December 2022) - Sun, Jia-Ming; Ho, Chia-Kang; Gao, Ya; Chong, Chio-Hou; Liu, Yang-Dan; Liu, Yu-Xin; Zheng, Dan-Ning; Zhang, Yi-Fan; Yu, Li
Abstract: Background: Autologous fat grafting is a common method for soft tissue defect repair. However, the high absorption rate of transplanted fat is currently a bottleneck in the process. Excessive inflammation is one of the main reasons for poor fat transplantation. Salvianolic acid B (Sal-B) is a herbal medicine that shows promise for improving the effectiveness of fat transplantation. Objective: The aim of this study was to improve fat graft survival by injecting Sal-B into fat grafts locally. Methods: In vivo, 0.2 mL of Coleman fat was transplanted into nude mice along with Sal-B. The grafts were evaluated by histologic analysis at 2, 4, and 12 weeks posttransplantation and by microcomputed tomography at 4 weeks posttransplantation. In vitro ribonucleic acid sequencing, cell proliferation assays, anti-inflammatory activity assays, molecular docking studies, and kinase activity assays were performed in RAW264.7 cells to detect the potential mechanism. Results: Sal-B significantly improved fat graft survival and attenuated adipose tissue fibrosis and inflammation. Sal-B also inhibited the polarization of M1 macrophages in fat grafts. In vitro, Sal-B inhibited the proliferation and activation of inflammatory pathways in RAW264.7 cells. In addition, Sal-B had an inhibitory effect on NF-κB (nuclear factor κ light polypeptide gene enhancer in B cells) signaling. This bioactivity of Sal-B may result from its selective binding to the kinase domain of the inhibitor of NF-κB kinase subunit β. Conclusions: Sal-B could serve as a promising agent for improving the effect of fat transplantation by inhibiting the polarization of M1 macrophages through NF-κB signaling.